2020
DOI: 10.4028/www.scientific.net/msf.989.335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Homogenization Heat Treatment and Cooling Modes on Microstructure of AA7475 Aluminum Alloy Ingot

Abstract: Microstructure evolution during the homogenization heat treatment of an Al-Zn-Cu-Mg (AA7475, which is typically used for the manufacture of aircraft design) alloy, was investigated using a combination of light microscopy, scanning electron microscopy (SEM), electron probe microanalysis (EPMA), X-ray diffraction (XRD) and differential scanning calorimetry (DSC). Ingots after different types (one-or two-steps treatments) of temperatures (from 380 to 510 °C) of homogenization and cooling conditions (cooling with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
2
Order By: Relevance
“…Compared with the H1 and H2 treatments samples, only Al 7 Cu 2 Fe and S(Al 2 CuMg) phases are observed in the H3 treatment sample, which means that σ [Mg(Zn, Al, Cu) 2 ] phase has dissolved completely after H3 treatment, whereas S(Al 2 CuMg) phase only has small amount. However, the investigation on influence of homogenization heat‐treatment and cooling modes on microstructure of AA7475 aluminum alloy ingot conducted by Reznik [ 24 ] is contradicting to our work. There may be two reasons for the discrepancies between these two studies, that is, on the one hand, high Cu content is reported to increase S(Al 2 CuMg) phase content remarkably; on the other hand, in our work, the holding time of 36 h was larger than the reported 24 h.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…Compared with the H1 and H2 treatments samples, only Al 7 Cu 2 Fe and S(Al 2 CuMg) phases are observed in the H3 treatment sample, which means that σ [Mg(Zn, Al, Cu) 2 ] phase has dissolved completely after H3 treatment, whereas S(Al 2 CuMg) phase only has small amount. However, the investigation on influence of homogenization heat‐treatment and cooling modes on microstructure of AA7475 aluminum alloy ingot conducted by Reznik [ 24 ] is contradicting to our work. There may be two reasons for the discrepancies between these two studies, that is, on the one hand, high Cu content is reported to increase S(Al 2 CuMg) phase content remarkably; on the other hand, in our work, the holding time of 36 h was larger than the reported 24 h.…”
Section: Resultscontrasting
confidence: 91%
“…phase only has small amount. However, the investigation on influence of homogenization heat-treatment and cooling modes on microstructure of AA7475 aluminum alloy ingot conducted by Reznik [24] is contradicting to our work. There may be two reasons for the discrepancies between these two studies, that is, on the one hand, high Cu content is reported to increase S(Al 2 CuMg) phase content remarkably; on the other hand, in our work, the holding time of 36 h was larger than the reported 24 h. Furthermore, S(Al 2 CuMg) phase also disappears completely while only Al 7 Cu 2 Fe phase remains in the H4-, H5-, and H6-treatment samples.…”
Section: Intergranular Phase Transformation and Distributioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The development of technologies for foundry and metal forming is directed towards the unification of several technological stages in one installation [1][2][3][4][5][6][7][8]. These include, for example, a horizontal semi-continuous casting machine (HSCCM) [9].…”
Section: Introductionmentioning
confidence: 99%